Dealing with Stress: Insights and Tips for Teenagers - Cognevich, Christie (Rowman & Littlefield Publishers, 2022)
Today's teenagers are dealing with stress at an unprecedented level. The inescapable flood of difficult news and world concerns can make anyone—but especially young adults—feel isolated and anxious. Dealing with Stress: Insights and Tips for Teenagers offers relatable anecdotes and practical strategies to guide teenagers who are struggling with stress and mental health, especially during the Covid-19 pandemic and other life crises. Readers will learn: What stress is and its function How and why it can impact young adults in particular How to identify and manage stress triggers A variety of coping methods The real-life experiences and advice of other teenagers Featuring sample mental health coping strategies and free downloadable blank guides on the author’s website (christiecognevich.com), Dealing with Stress is a valuable resource, empowering teenagers to recognize and manage the stress factors in their lives.